Perubahan Perilaku Wisatawan Domestik Pada Destinasi The Lodge Maribaya Sebelum Dan Sesudah Pandemi Covid-19 - Muhammad Akmal Muarif; Ina Ratnasari (Peneliti.net, 2023)
The Covid-19 pandemic has had an impact on changes in the economy to tourism. Due to the virus caused by Covid-19, various tourism areas have to be temporarily closed. From the policy set by the government, namely the Large-Scale Social Enforcement, where tourists cannot travel or visit various tours. However, over time the government implemented a new policy, namely the New Normal. Tourists who want to travel can still travel but with new regulations, namely implementing health protocols. The tourists also change their behavior patterns by complying with the policies set by the government. The research that we conducted used quantitative methods with questionnaires media.